2015
DOI: 10.1021/jacs.5b03192
|View full text |Cite
|
Sign up to set email alerts
|

Trap-Free Halogen Photoelimination from Mononuclear Ni(III) Complexes

Abstract: Halogen photoelimination reactions constitute the oxidative half-reaction of closed HX-splitting energy storage cycles. Here, we report high-yielding, endothermic Cl2 photoelimination chemistry from mononuclear Ni(III) complexes. On the basis of time-resolved spectroscopy and steady-state photocrystallography experiments, a mechanism involving ligand-assisted halogen elimination is proposed. Employing ancillary ligands to promote elimination offers a strategy to circumvent the inherently short-lived excited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 39 publications
4
133
0
Order By: Relevance
“…Depicted in Scheme is one of the possible reaction pathways for the formation of 3 aa , which is tentatively proposed on the basis of our mechanistic studies and the related studies previously reported . Initially, NiCl 2 (dtbbpy) is photo‐reduced to Ni I species 9 .…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…Depicted in Scheme is one of the possible reaction pathways for the formation of 3 aa , which is tentatively proposed on the basis of our mechanistic studies and the related studies previously reported . Initially, NiCl 2 (dtbbpy) is photo‐reduced to Ni I species 9 .…”
Section: Methodssupporting
confidence: 58%
“…The resulting Ni I species 9 undergoes oxidative addition of 2 a to furnish Ni III species 10 . The Ni III 10 absorbs a photon to be excited, leading to homolysis of the Ni−Br bond . Ni II 11 is produced together with a bromo radical, which abstracts a benzylic hydrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The focus placed on the 'source' of advanced crystallography techniques allows students to learn what crystallography can do for their research and to network with professionals who can potentially provide a valuable collaboration. Students are typically keen to take advantage of such resources once they become available and apply what they have learned to complete their research projects (Das et al, 2017;Feng et al, 2017;Hwang et al, 2015;Lou et al, 2016;Powers et al, 2013Powers et al, , 2016Powers, Anderson et al, 2014;Ramadhar et al, 2015aRamadhar et al, ,b, 2017. A list of example beam time proposals that students submitted for their own research projects at two major user research facilities can be found in Table S1 in the supporting information.…”
Section: Impactmentioning
confidence: 99%
“…Chlorine radicals are known to form stabilized adducts with aromatic functional groups. 9,10 Therefore, we reasoned that if benzene were utilized as a solvent, we could promote the desired photoelimination and simultaneously prevent competitive solvent C(sp 3 )–H abstraction. We recognized that the ability to use an inert solvent and limiting C–H coupling partner would be highly desirable, facilitating the application of this manifold to a broad range of C–H coupling partners under general reaction conditions.…”
mentioning
confidence: 99%